2010
DOI: 10.1007/s00213-010-1855-2
|View full text |Cite
|
Sign up to set email alerts
|

Dose-effect study of Gelsemium sempervirens in high dilutions on anxiety-related responses in mice

Abstract: IntroductionThis study was designed to investigate the putative anxiolytic-like activity of ultra-low doses of Gelsemium sempervirens (G. sempervirens), produced according to the homeopathic pharmacopeia.MethodsFive different centesimal (C) dilutions of G. sempervirens (4C, 5C, 7C, 9C and 30C), the drug buspirone (5 mg/kg) and solvent vehicle were delivered intraperitoneally to groups of ICR-CD1 mice over a period of 9 days. The behavioral effects were assessed in the open-field (OF) and light–dark (LD) tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
131
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 83 publications
5
131
1
2
Order By: Relevance
“…The fact that G. sempervirens was completely inactive in the Light Dark test, and the evidence of diazepam-induced opposite effects was considered merely secondary. Magnani et al (2010) reached the same conclusion even though G. sempervirens modified mice behaviour in the Light Dark test without influencing behaviour in the center of the Open Field. It is more complicated here to determine the effect of buspirone since the dose significantly reduced spontaneous locomotor activity.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The fact that G. sempervirens was completely inactive in the Light Dark test, and the evidence of diazepam-induced opposite effects was considered merely secondary. Magnani et al (2010) reached the same conclusion even though G. sempervirens modified mice behaviour in the Light Dark test without influencing behaviour in the center of the Open Field. It is more complicated here to determine the effect of buspirone since the dose significantly reduced spontaneous locomotor activity.…”
supporting
confidence: 65%
“…Diazepam, used as a standard anxiolytic drug, was completely ineffective on mouse behaviour in the Open Field, but increased the time in the light compartment and transitions in the Light Dark test (see Tables 1 and 2, p. 4). When the G. sempervirens 5 C, 7 C and 30 C dilutions were evaluated in another strain of mice (C57BL/6J), again, the opposite effect from that reported by Magnani et al (2010) was found. G. sempervirens centesimal dilutions modified mice behaviour in the Open Field (Table 3, Bellavite et al 2009a p. 5).…”
mentioning
confidence: 49%
“…Changes in lifestyle and diet are an increasingly used approach for treating anxiety disorders [5]. Recent studies in experimental animals have shown that some homeopathic remedies have an anxiolytic effect comparable to conventional pharmacological treatments [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…At very high dilution levels (beyond the Avogadro limit) the probability of the presence of molecules of the original substance is near to zero (Marschollek et al 2010). This aspect represents one of the reasons why the biological effectiveness of EDS is still controversial, although there is emerging evidence for their in vitro activity (Brizzi et al , 2011Belon et al 2004;Witt et al 2007;Frenkel et al 2010;Endler et al 2011) as well as in vivo activity (Bellavite et al 2006;Welles et al 2007;Baumgartner et al 2008;Shah-Rossi et al 2009;Betti et al 2010;Jäger et al 2010;Magnani et al 2010;Wyss et al 2010). Based on physico-chemical measurements, it was hypothesized that the particular preparation technique of EDS could lead to a structural alteration of the aqueous solvent that appears to trigger the formation of molecular aggregates of water molecules (Samal and Geckeler 2001;Elia et al * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%